A Biocompatible Therapeutic Catheter‐Deliverable Hydrogel for In Situ Tissue Engineering. Issue 5 (4th February 2019) - Steele, Amanda N.; Stapleton, Lyndsay M.; Farry, Justin M.; Lucian, Haley J.; Paulsen, Michael J.; Eskandari, Anahita; Hironaka, Camille E.; Thakore, Akshara D.; Wang, Hanjay; Yu, Anthony C.; Chan, Doreen; Appel, Eric A.; et al.
Abstract: Hydrogels have emerged as a diverse class of biomaterials offering a broad range of biomedical applications. Specifically, injectable hydrogels are advantageous for minimally invasive delivery of various therapeutics and have great potential to treat a number of diseases. However, most current injectable hydrogels are limited by difficult and time‐consuming fabrication techniques and are unable to be delivered through long, narrow catheters, preventing extensive clinical translation. Here, the development of an easily‐scaled, catheter‐injectable hydrogel utilizing a polymer–nanoparticle crosslinking mechanism is reported, which exhibits notable shear‐thinning and self‐healing behavior. Gelation of the hydrogel occurs immediately upon mixing the biochemically modified hyaluronic acid polymer with biodegradable nanoparticles and can be easily injected through a high‐gauge syringe due to the dynamic nature of the strong, yet reversible crosslinks. Furthermore, the ability to deliver this novel hydrogel through a long, narrow, physiologically‐relevant catheter affixed with a 28‐G needle is highlighted, with hydrogel mechanics unchanged after delivery. Due to the composition of the gel, it is demonstrated that therapeutics can be differentially released with distinct elution profiles, allowing precise control over drug delivery. Finally, the cell‐signaling and biocompatibility properties of this innovative hydrogel are demonstrated, revealing its wide range of therapeutic applications. Abstract : A shear‐thinning, biocompatible, dual‐phase hydrogel family based on polymer–nanoparticle interactions is developed in this report. These self‐assembled hydrogels advance the field of shear‐thinning gels due to their 1) notable shear profile, 2) ability to be delivered through a clinically relevant catheter, 3) biocompatibility, and 4) dual‐phase drug release behavior.